SIKAP BERBAHASA SISWA SD PADA PEMBELAJARAN TEMATIK DI ERA DIGITAL 5.0 - Ari Rohmawati; Dian Pratiwi; Siti Zubaedah; Santi Hendayani (LP3M Universitas Muhammadiyah Muara Bungo, 2022)
Regional languages often interfere with the use of Indonesian in the learning process. Whereas the use of language in the classroom is a kind of official situation. Teachers and students who are language users are requir to use standard language during the teaching and learning process in class. The purpose of this study was to describe the language attitudes of elementary school students in thematic learning in the digital era 5.0. This research uses a phenomenological study approach. Researchers describe the language attitudes of elementary school students in thematic learning in the digital era 5.0. The language attitude of elementary school students in Pesawaran Regency includes feeling pride in being mastered and accepting a language for a language. A sense of pride in Indonesian is also shown by the use of Indonesian in learning, Javanese vocabulary appears. positive attitude towards the Indonesian language by using Indonesian to ask the teacher, answer questions from the teacher, how to learn with friends in learning.